Psychiatric Correlates of HAART Utilization and Viral Load Among HIV-Positive Impoverished Persons - Carrico, Adam W. (2011)
OBJECTIVE: Research on the role psychiatric factors in HIV disease management has yielded discrepant findings, possibly because prior studies did not include comprehensive psychiatric screeners. This study administered a validated screener to examine psychiatric correlates of highly active anti-retroviral therapy (HAART) utilization and viral load. DESIGN: Community-recruited, HIV-positive impoverished persons provided sociodemographic information, completed a Diagnostic Interview Schedule that screened for psychiatric disorders, and provided a blood sample to measure HIV disease markers. METHODS: In this cross-sectional investigation with 227 participants, a multiple logistic regression model examined correlates of HAART utilization compared to a reference group that was eligible for (i.e., CD4+ count ≤ 350 cells/μl) but not taking HAART. A multiple linear regression model examined correlates of HIV viral load among 147 participants on HAART. RESULTS: Sleeping on the street (Adjusted OR [AOR] = 0.06; 95% CI = 0.01 – 0.26) and screening positive for a stimulant use disorder (AOR = 0.29; 95% CI = 0.13 – 0.65) were independently associated with lower odds of HAART utilization. Conversely, enrollment in the AIDS Drug Assistance Program (AOR = 3.94; 95% CI = 1.45 – 10.73) and receipt of mental health treatment (AOR = 4.78; 95% CI = 1.77 – 12.87) were independently associated with increased odds of HAART utilization. Among those on HAART, screening positive for a severe mental illness was independently associated with a 6-fold higher viral load. CONCLUSIONS: Providing psychiatric treatment could optimize health outcomes among HIV-positive impoverished persons and boost the effectiveness of “Test and Treat” approaches to HIV prevention.